A conceptual reappraisal of risks in the implementation of BRI after COVID‐19: Best strategies to learn for CMNEs in BRI projects. (14th February 2023) - Sheetal,; Narang, Daviender; Singh, Gursimranjit
Abstract: This study is aimed to propose a quantitatively supported framework regarding different types of risks involved in BRI and strategic solutions to neutralize the risks. The conceptual model and related propositions are advanced, based on bibliometric and science mapping analysis of 367 articles published over 6 years about risk, success, failure and dissent about the projects, and strategies to mitigate these risks. The descriptive statistics and science mapping approaches using co‐citation analysis were performed with VOSviewer software. A co‐citation analysis, coupled with content analysis of most co‐cited articles, uncovered four underlying research streams, including "Infrastructural expansion and political & economical risks, " "Investment choice through impact assessment and cultural risks, " "Environmental risks, " and "Real outcomes of BRI projects and viewpoint of host countries." Among the four strategies identified, developing trust in the Chinese system can be created through National Branding by Chinese MNEs to mitigate the geo‐political risks. Second, Guanxi neutralizes the reputation risks and cultural friction in collaborative projects and positively affects BRI project implementation. Third, the localization of management and processes can also help in offsetting the environmental risks in post COVID scenario. Lastly, increasing multilateral funding for sustainable infrastructure can be used to boost financial capacity building and mitigate financial risk to a certain extent. The present study has been a novel attempt to relate current research themes to emerging areas under BRI. This study is one of its kind which focuses on reshaping the views of practitioners, researchers, and policymakers on the multifaceted areas and themes in the BRI research field, to examine the risks and a roadmap for future research.